SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA GURU MENGGUNAKAN METODE MULTI ATTRIBUTE UTILITY THEORY DI SMAN 1 NGANTANG BERBASIS WEB - Lailatul Mukaromah; Lazulfa, Indana; Achmad Imam Agung; Didiek Rusdyanto (Inovate, 2024)
A teacher plays a very important role in improving the quality of education for students at school. The qualityof education at school can be assessed from the level of quality of teachers in carrying out various activities,roles and responsibilities at school. One of the ways that schools and education agencies can improve thequality of education is by conducting teacher performance assessments, to determine the quality of teacherperformance. Therefore, evaluating teacher performance is very important, so that teachers can alwaysimprove their role in every student at school. Unfortunately, the teacher performance assessment process atSMAN 1 Ngantang is still manual, intuitive and less than objective, so the assessment results are stillconsidered unsatisfactory. Because of this, it is important to build a Decision Support System for TeacherPerformance Assessment at SMAN 1 Ngantang, to make it easier for schools to assess teacher performanceat school. Calculations in this system will use the MAUT method, this method was chosen because it canassess and rank alternatives based on the preference values and weights that have been given to each criterion.Keywords: Decision Support System, Teacher Performance Assessment, MAUT Method